Phytochemical and pharmacological activities of Commiphora gileadensis: A review - Mokaizh, A. A.; Nour, Abdurahman Hamid; Rosli, Mohd Yunus; Siti Qurratu' Aini, Mahat; Elnour, Ahmed A. M.; Modather, Rayan H. (Universiti Malaysia Pahang, 2024)
Background: Commiphora gileadensis is an important medicinal plant with a variety of uses in medicine. Secondary phytoconstituents of the plant are medicinally important through their pharmacological actions, which include antioxidant, antibacterial, cytotoxic, anti-cancer, and antiviral properties. Objective: The aim of this review is to identify the phytochemical, pharmacological, and toxicological properties of the C. gileadensis. Method: The study’s review methodology is based on a thorough search of the literature, with data drawn from book chapters, research articles, review articles, and conference papers. Results: According to the findings, pharmacological studies support the use of C. gileadensis extracts in folk medicine, where the phytochemical research revealed that this plant is high in saponins, flavonoids, proteins, triterpenes, lipids, sterols, fibers, amino acids. Conclusion: As a result, this review presented an overview of C. gileadensis’ bioactive components, phytochemical and pharmacological capabilities, as well as its toxicity. The review suggests that more attention be paid to the stem, bark, and leaf of C. gileadensis because extending research materials could lead to the discovery of novel bioactive components.